2021
DOI: 10.1101/2021.04.22.440927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acoustic properties across the human skull

Abstract: Transcranial ultrasound is emerging as a noninvasive tool for targeted treatments of brain disorders. Transcranial ultrasound has been used for remotely mediated surgeries, transient opening of the blood-brain barrier, local drug delivery, and neuromodulation. However, all applications have been limited by the severe attenuation and phase distortion of ultrasound by the skull. Here, we characterized the dependence of the aberrations on specific anatomical segments of the skull. In particular, we measured ultra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Across 8 ex-vivo skulls, we found that the ultrasound intensity delivered into a deep brain location (see Methods) is attenuated by a factor of 11.4 ± 6.8 (mean±S.D. ), which replicates previous findings 43 . In principle, the attenuation could be estimated using tabulated values (e.g., 20,21 ), but the high variability of the attenuation across individuals makes such estimates inaccurate and uncertain (Fig.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Across 8 ex-vivo skulls, we found that the ultrasound intensity delivered into a deep brain location (see Methods) is attenuated by a factor of 11.4 ± 6.8 (mean±S.D. ), which replicates previous findings 43 . In principle, the attenuation could be estimated using tabulated values (e.g., 20,21 ), but the high variability of the attenuation across individuals makes such estimates inaccurate and uncertain (Fig.…”
Section: Resultssupporting
confidence: 87%
“…RTT is limited to transducer geometries and sections of the skull for which a through-transmit path can be established. We chose to place transducers parallel over the left and right sides of the skull as 1) there is a through-transmit path with minimal incidence angle to the skull 2) the parietal bone has favorable acoustic properties 19 , and 3) this geometry provides convenient coupling. Deviations from this geometry may incur loss of performance or practicality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pressure transmission coefficient T S was calculated with T S = √ E L . The values of T S calculated with each of the different mapping approaches were compared against experimental values of sub-MHz pressure transmission (T E ) from literature reports on pressure [18,29,[32][33][34][35][36] and energy [28,37,38] transmission. For the latter, T E was approximated by the square root of the reported energy transmission.…”
Section: Modelingmentioning
confidence: 99%
“…Computational skull modeling, derived from each subject’s head CT or brain MRI, is a complex process which is currently being developed and validated with ongoing studies. 40-42 Further study in this area will also allow for use of LIFUS in a (paradoxically) less focused manner, to perhaps treat a broader area of cortex known to be epileptogenic, such as in some frontal lobe and other epilepsies.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%